Implementasi Hysterisis Current Control Pulse Witdh Modulation (HCCPWM) Untuk Inverter 3 Fasa - Tri Yogi Putra; Muldi Yuhendri (Jurnal Teknik Elektro Indonesia, 2021)
Based on the source used, there are several types of converters, one of which is a voltage source converter (VSC). In this study, using a converter that can work as an inverter. In industry, an inverter is useful for supplying the AC voltage source from industrial plants with DC sources, by varying the voltage and output frequency of the inverter. The method used is the HCCPWM generation method or Hysterisis Current Control Pulse Witdh Modulation. This method was chosen because it has several advantages which are good stability, very fast transient response and good accuracy. To activate HCCPWM, a 3 phase reference current signal is first made in the Matlab Simulink, this reference current is then compared with the actual current from the current sensor, then the error is controlled with the hysteresis band. In Arduino mega2560, the pulses generated by HCCPWM in the Matlab Simulink are converted into a duty cycle. The modulated pulse generated by the Arduino PWM pin will be increased using a gate drive circuit, so that the voltage is obtained according to the voltage required by the Mosfet to activate the switch. The results of the tests that have been done show that the voltage source converter (VSC) designed in this study has worked well as intended. This can be seen from the actual current from the current sensor which has been compared with the reference voltage using the HCCPWM method which is included in the Simulink Matlab program.